2016
DOI: 10.1007/s12560-016-9275-z
|View full text |Cite
|
Sign up to set email alerts
|

New Proof-of-Concept in Viral Inactivation: Virucidal Efficacy of 405 nm Light Against Feline Calicivirus as a Model for Norovirus Decontamination

Abstract: The requirement for novel decontamination technologies for use in hospitals is ever present. One such system uses 405 nm visible light to inactivate microorganisms via ROS-generated oxidative damage. Although effective for bacterial and fungal inactivation, little is known about the virucidal effects of 405 nm light. Norovirus (NoV) gastroenteritis outbreaks often occur in the clinical setting, and this study was designed to investigate potential inactivation effects of 405 nm light on the NoV surrogate, felin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 47 publications
8
82
1
2
Order By: Relevance
“…Future work could investigate other protozoa which are harmful to human health such as Blastocystis hominis, Cryptosporidium parvum, Entamoeba histolytica and Giardia lamblia (91). Additionally, results by Tomb et al (25) are currently the only published evidence of the virucidal efficacy of 405 nm light against mammalian viruses, demonstrating that very high doses (~700 J cm À2 ) are required for 1 log 10 inactivation when in minimal media (Dulbecco's phosphate-buffered saline). Similarly, inactivation of a Streptomyces bacteriophage, φC31, required high doses of 405 nm light when suspended in minimal media (1020 J cm À2 calculated for a 1 log 10 reduction) (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work could investigate other protozoa which are harmful to human health such as Blastocystis hominis, Cryptosporidium parvum, Entamoeba histolytica and Giardia lamblia (91). Additionally, results by Tomb et al (25) are currently the only published evidence of the virucidal efficacy of 405 nm light against mammalian viruses, demonstrating that very high doses (~700 J cm À2 ) are required for 1 log 10 inactivation when in minimal media (Dulbecco's phosphate-buffered saline). Similarly, inactivation of a Streptomyces bacteriophage, φC31, required high doses of 405 nm light when suspended in minimal media (1020 J cm À2 calculated for a 1 log 10 reduction) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a small number of bacterial endospores, fungi and yeasts have been inactivated using violet-blue light (16)(17)(18)(19)(20)(21)(22)(23). To date, little is known about viral susceptibility; however, there is now published evidence demonstrating 405 nm light inactivation of a viral surrogate, bacteriophage ɸC31, and a mammalian virus, feline calicivirus, without the requirement of additional photosensitizers (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tomb et al determined the viricidal efficacy of 405-nm aBL using feline calicivirus suspended in a minimal medium (DPBS) or several organically-rich media (Tomb et al, 2016). In DPBS, a 4-log 10 plaque forming units (PFU) reduction was observed after an aBL exposure of 2.8 kJ/cm 2 (irradiance 155.8 mW/cm 2 ).…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…These toxic species cause widespread oxidative damage to the pathogens, which ultimately leads to death of pathogens (16)(17)(18). This decontamination method has efficacy against a wide range of pathogenic organisms including vegetative bacteria, spore forming bacteria and fungi (17,19,20), with recent studies also demonstrating the potential for inactivation of viruses, protozoa, and parasites (21)(22)(23). Additionally, 405 nm light is safer than UV light wavelengths, with antimicrobial efficacy capable of being achieved at levels that are compatible with mammalian cells (16,(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (29) reported the successful reduction of bacterial contamination within human blood plasma using 405 nm light, and significantly, demonstrated the capacity for this decontamination treatment to be applied to the plasma whilst in situ within the transfusion bag, highlighting a potential operational advantage for this prospective PRT. Antiviral efficacy has also been indicated, with successful reduction of a model virus (calicivirus) in small volume plasma samples artificially seeded with the virus (22).…”
Section: Introductionmentioning
confidence: 99%